Influencia de la creatividad en el desarrollo de las habilidades cognitivas en estudiantes del octavo año año de educación General básica paralelos A,B,C, de la unidad educativa Juan Montalvo de Machala periodo lectivo 2013-2014. - Barreto Ibarra, Nuria Patricia (2014)
When we look around, the mind begins to structure and assimilate reality, so that it is a dynamic process that allows a subject to relate to reality, thanks to the imagination, the human being is able to develop ideas to originate responses to situations Which is presented to you.